Cultural Value and Locality in the Merapi Daily Short Story Collection “Lintang Johar Cikal Bakal Mataram Islam” - Agung Tri Laksono; Else Liliani (Britain International for Academic Research (BIAR) Publisher, 2023)
Cultural Values And Locality In The Collection Of Daily Merapi Short Stories “Lintang Johar Cikal Bakal Mataram Islam” By Iis Suwartini. The presence of literary works is closely related to the culture that exists in society. Literary works exist as a means to invite people to live in tune with the existing culture. In line with this, this study aims to determine the values of Javanese culture and locality contained in the Kumoulan Kompas Daily Short Story